The Construction of Mental Health Discourse In The Lyrics of The Song “Membasuh” By Hindia: A Critical Discourse Analysis By Norman Fairclough - Novitasari Situmorang (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This qualitative study explores the construction of mental health discourse within the Indonesian popular song “Membasuh” by Hindia featuring Rara Sekar, using Norman Fairclough’s three dimensional Critical Discourse Analysis framework. Through a comprehensive investigation integrating textual structure, discursive practice, and socio cultural practice, the research demonstrates how popular music functions as an influential counter hegemonic cultural artifact. At the textual level, micro linguistic features, spiritual metaphors, and relational process clauses systematically reframe emotional vulnerability from an institutionalized sign of weakness into a legitimate, shared human condition. At the discursive level, egalitarian production dynamics and digital distribution platforms bypass traditional gatekeepers, facilitating active audience decoding and transforming passive listening into a collective cathartic practice. At the socio cultural level, the song directly critiques deep seated societal stigmas surrounding youth mental health, offering an alternative framework of unconditional empathy and mutual care amidst structural healthcare deficits in contemporary Indonesia. Ultimately, the findings reveal that independent popular music serves as a vital platform for social solidarity, psychological healing, and the subversion of dominant cultural norms.